Distribution of traditions and styles of rock art paintings – a preliminary comparative analysis between sites in the Complex of Chapada Diamantina and Depressão Sertaneja Meridional of the Caatinga Biome - Kachimareck, Claudia Cunha (SITIENTIBUS série Ciências Biológicas, 2007)
The ecoregions of the Complex of Chapada Diamantina and Depressão Sertaneja Meridional of the Caatinga Biome present a remarkable stylistic variety as well as evident differences between one region and the other in terms of rock art production. This article presents the results of first hand comparative observations of 122 rock art sites in both regions. Those were carried out between 1999 and 2006. A new style of rock art limited to the Complex of Chapada Diamantina is also introduced: Aquitã style.